Implementasi Aplikasi E-Planning Dalam Meningkatkan Kinerja Pegawai (Studi Kasus Bappeda Sumut) - Putri Ramadhani; Zainarti Zainarti; Muhammad Ikhsan Harahap (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The purpose of this study is to find out how the implementation of the E-Planning application in the Regional Development Planning Agency (BAPPEDA) of North Sumatra, the obstacles in implementing the e-planning system. This type of research is a qualitative descriptive study using interviews in data collection. The research method used in this study uses a qualitative research type with locations in North Sumatra BAPPEDA. The methods used are observation, interviews, and documentation. The results of the study show that in practice the implementation of the e-planning system has been carried out well, but there are several obstacles, namely, human resources that are not evenly distributed in regional development planning, inconsistency in development planning due to political pressure and frequent changes that occur. The way for North Sumatra BAPPEDA to overcome these obstacles is by conducting training, implementing e-planning and following changes quickly and precisely.